Filmmakers to Themselves? Czech Documentary Cinema After 2000 - Lucie Česálková (Images)
The development of Czech post-socialist documentary cinema was significantly influenced by the process of privatization of Short Film (the former resource base for documentary filmmaking). In the early 1990s, the documentary, as a rather unprofitable area of filmmaking, was not a priority for the rapidly developing field of domestic production. As such, documentary was fully dependent on collaboration with the television industry. This study, however, focuses mainly on the period after the year 2000, and analyses its main trends. Special attention is paid to the establishment of new institutions to support the development and production of film, as well as new marketing and exhibition platforms. Documentary filmmaking in a small post-socialist country is here treated as being embedded in and influenced by a web of inter-relations between filmmakers, Czech Television, the Institute of Documentary Cinema and the Jihlava International Documentary Film Festival. l